Novel regulation mechanism of histone methyltransferase SMYD5 in rheumatoid arthritis - Chenxi Xiao; Zhenghua Su; Jialin Zhao; Subei Tan; Mengting He; Yuhui Li; Jiayao Liu; Jie Xu; Yajie Hu; Zhongzheng Li; Chunxiang Fan; Xinhua Liu (Cellular & Molecular Biology Letters)
Abstract Background Fibroblast-like synoviocytes (FLS) are crucial for maintaining synovial homeostasis. SMYD5, a member of the histone lysine methyltransferase subfamily SMYDs, is involved in many pathological processes. This study aimed to investigate the role of SMYD5 in regulating synovial fibroblast homeostasis and the pathogenesis of rheumatoid arthritis (RA). Methods Proteomic screening was conducted to assess SMYD5 expression in the synovium of patients with osteoarthritis (OA) and RA. In vitro, interleukin-1 beta (IL-1β) was used to induce proliferation and inflammation in FLS. Further, we performed loss-of-function and gain-of-function experiments to investigate the biological function of SMYD5. In vivo, adeno-associated virus (AAV) vectors carrying SMYD5 short-hairpin RNA (AAV-shSMYD5) were injected into the knee joints to knock down SMYD5 in a collagen-induced arthritis (CIA) mouse model to evaluate its role in joint damage. Results We observed a significant elevation of SMYD5 expression in the synovial tissues of patients with RA and IL-1β-induced FLS. SMYD5 facilitated posttranslational modifications and activated downstream signaling pathways, thereby promoting proliferation and inflammation in FLS. Mechanistically, SMYD5 mediated the methylation of Forkhead box protein O1 (FoxO1), which accelerated its degradation through ubiquitination, resulting in substantial FLS proliferation. Additionally, SMYD5 promoted lactate release to activate NF-κB signaling pathways by upregulating hexokinases-2 (HK2) expression, a key glycolytic enzyme, thereby intensifying the inflammatory response in FLS. Supporting these findings, intraarticular delivery of AAV-mediated SMYD5 knockdown in the CIA mice model effectively alleviated joint swelling, bone erosion, and overall arthritis severity. Conclusions Together, these findings suggest that SMYD5 is a dual target for regulating synovial fibroblast homeostasis and the pathogenesis of RA. Targeting SMYD5 through local treatment strategies may provide a novel therapeutic approach for RA, particularly when combined with immunotherapy. Graphical abstract